Front Cover: Optical Super‐Localisation of Single Nanoparticle Nucleation and Growth in Nanodroplets (ChemElectroChem 9/2023). Issue 9 (20th April 2023) - Ciocci, Paolo; Valavanis, Dimitrios; Meloni, Gabriel N.; Lemineur, Jean‐François; Unwin, Patrick R.; Kanoufi, Frédéric
Abstract : The Front Cover draws a parallel between the hybrid scanning electrochemical cell microscopy‐interference reflection microscopy (SECCM‐IRM) technique, and its use to monitor the nucleation and growth of silver nanoparticles, and the recording of a performance by a rock band. The stage corresponds to the meniscus‐electrode wetted area formed with the SECCM probe. It is illuminated by optical lighting. Silver particles rock and roll ; they are dynamic and interact with each other just like the band. The behaviour of each individual particle is revealed through optical‐guided localisation, just as post‐processing in a multitrack sound recording can be used to isolate individual tracks. Cover design by Somersault18:24. More information can be found in the Research Article by P. Ciocci, D. Valavanis et al .